EMPLOYEE PERFORMANCE ANALYSIS : A CASE STUDY IN NORTH MALUKU - Prince Charles Heston Runtunuwu; Lev Horodyskyj (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2023)
The purpose of this study was to determine the effect of partially and simultaneously variables of work discipline, leadership style and work experience on the performance of employees of the Tidore District Office, Tidore Islands City. The total target population is 108 respondents. The questionnaires returned were 104 respondents which were used as research data analysis. The analysis model used to test the hypothesis is multiple linear regression analysis and uses SPSS as a statistical test tool. The results of the study found that: (1) Work Discipline has a positive and significant effect on employee performance. This means that higher / better work discipline causes an increase in the performance of Tidore District Office employees, (2) Leadership Style has a positive and significant effect on employee performance. This means that the higher / better the leadership style causes an increase in the performance of Tidore District Office employees, (3) Work experience has a positive and significant effect on employee performance. This means that the higher / better the experience, and (4) Work Discipline, Leadership Style and Work Experience together have a positive and significant effect on the performance of the Tidore District Office employees, Tidore Islands City.